Some new records of fungi associated with salfi palm (Caryota urens) - VERMA, R.K. (Indian Phytopathology, 2002)
A new species which was collected from rachis of C. urens in Madhya Pradesh, India, is described, illustrated and compared with allied species. The name Diatrypella caryotae is proposed. Ganoderma applanatum was associated with mature and dried palmand C. urens is thought to be a new host for this pathogen. Rhizostilbella hibisci was associated with root rot of 1-year-old seedlings and is thought to be a new fungal record for India.